1996
DOI: 10.1002/j.1460-2075.1996.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential ligand-dependent interactions between the AF-2 activating domain of nuclear receptors and the putative transcriptional intermediary factors mSUG1 and TIF1.

Abstract: Using a yeast two‐hybrid system we report the isolation of a novel mouse protein, mSUG1, that interacts with retinoic acid receptor alpha (RAR alpha) both in yeast cells and in vitro in a ligand‐ and AF‐2 activating domain (AF‐2 AD)‐dependent manner and show that it is a structural and functional homologue of the essential yeast protein SUG1. mSUG1 also efficiently interacts with other nuclear receptors, including oestrogen (ER), thyroid hormone (TR), Vitamin D3 (VDR) and retinoid X (RXR) receptors. By compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
253
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(269 citation statements)
references
References 75 publications
13
253
1
2
Order By: Relevance
“…This selectivity is consistent with previous studies on putative mammalian mediators, which revealed their differential interaction with the AF-2 ADs of various NRs in spite of the similarity of their respective AF-2 AD core motif (vom Baur et al 1996;Thé not et al 1997). Thus, the activity of the RAR␣ AF-2 constructs that can activate transcription in a RA-dependent manner in yeast (Heery et al 1993) is probably not mediated by Ada3.…”
Section: Ada3 a Coactivator/mediator For The Ligand-dependent Activasupporting
confidence: 92%
“…This selectivity is consistent with previous studies on putative mammalian mediators, which revealed their differential interaction with the AF-2 ADs of various NRs in spite of the similarity of their respective AF-2 AD core motif (vom Baur et al 1996;Thé not et al 1997). Thus, the activity of the RAR␣ AF-2 constructs that can activate transcription in a RA-dependent manner in yeast (Heery et al 1993) is probably not mediated by Ada3.…”
Section: Ada3 a Coactivator/mediator For The Ligand-dependent Activasupporting
confidence: 92%
“…Surprisingly, we found that Hr interacts with TR. Previously identified proteins that interact with TR have been shown to interact with multiple nuclear receptors (9,10,(14)(15)(16)(17)(18)(19)(20)(21). In contrast, of the retinoid and steroid receptors tested here, Hr interacts only with TR.…”
mentioning
confidence: 79%
“…Target gene activation is not required for catabolism (Zhu et al, 1999). The activated AF-2 domain was previously shown to bind the SUG-1 component of the proteasome 19 S complex vom Baur et al, 1996), providing a direct link between AF-2 activation and the proteasome-dependent degradation ( Figure 1). Not surprisingly, given the universal use of the AF-2 domain in nuclear receptors, such ligand-induced nuclear receptor catabolism has been described for a number of them (ERa, PPARg, PR.…”
Section: The Playersmentioning
confidence: 93%
“…We had proposed that RA-induced, AF-2 dependent, degradation of the normal RARa could derepress targets independently of an AF-2-dependent transcriptional activation (Zhu et al, 1999). Taken that the molecular determinants in the receptor required for coactivator binding and degradation are very similar, if not identical (vom Baur et al, 1996;Zhu et al, 1999), it may not be so easy to discriminate between the activation and the derepression models. Assuming that derepression through degradation is indeed critical for di erentiation induction, arsenic, which selectively degrades PML/RARa, could act through the same process.…”
Section: What Are the Functional Consequences Of Pml/rara Degradationmentioning
confidence: 99%